Large-eddy simulation of a natural gas direct injection spark ignition engine with different injection timings. (15th February 2023) - Yosri, MohammadReza; Kar, Tanmay; Talei, Mohsen; Gordon, Robert L.; Brear, Michael J.; Khosravi, Maziar
Abstract: This paper presents a large-eddy simulation (LES) study of a compressed natural gas (CNG) direct injection spark ignition (DISI) engine with different injection timings. Three cases with late, moderate and advanced injection timings are investigated to examine fuel/air mixing and combustion characteristics of a CNG DISI engine. A transition flame speed approach is used in which the flame propagates like a laminar flame until it reaches a specified kernel size and then develops as a turbulent flame. Changing the transition kernel size significantly affects both the in-cylinder pressure trace and the mass fraction burned (MFB) profile, highlighting the importance of correctly capturing the early stage of flame development. Different injection timings result in varying levels of mixing and homogeneity within the cylinder. Although more time is available for mixing in the most advanced injection case, the jet impingement on the piston crown increases the level of mixture in-homogeneity. It is shown that the variation of the laminar flame speed as a result of mixture in-homogeneity is the primary factor affecting flame propagation for different injection timings. Highlights: To predict the burn rate, it is essential to correctly capture the early stage of flame development. Different injection timings result in varying levels of homogeneity within the cylinder and therefore, different burn rates. The primary factor influencing flame propagation for cases with different injection timings was mixture homogeneity. Intermediate injection timing, featuring the highest level of homogeneity, resulted in optimal engine performance.